ApoE Receptors in the Nervous System - Herz, Joachim (2009)
PURPOSE OF REVIEW: Over the last few years ApoE receptors, also known as LDL receptor related proteins, have distinguished themselves as functionally diverse signaling receptors with pivotal roles not only in the vascular system, but also in the nervous system and during development. RECENT FINDINGS: The expanding roles of ApoE receptors for cellular signal transduction at the same time transcend and integrate their lipid transport roles into a larger biological and clinical context. ApoE receptors are essential for the development of the nervous system, the regulation of synaptic plasticity, neuroprotection, and the innervation of the muscle. They also regulate the metabolism of the amyloid precursor protein on multiple levels, implicating them in the pathogenesis of Alzheimer's disease (AD). SUMMARY: ApoE, a common ligand for all members of the evolutionarily ancient LDL receptor gene family, is the major genetic modifier of the age of onset of Alzheimer's disease. The underlying molecular mechansims remain shrouded in mystery, but the numerous critical functions of ApoE receptors within and outside the nervous system that have recently emerged make it likely that these multifunctional signal modulators participate in AD pathogenesis. This review attempts to summarize the most recent and relevant findings in this area.